The grammar of ‘transform’ and ‘social transformation’: a systemic functional study - Christian M.I.M. Matthiessen; Jesús David Guerra-Lyons; Francisco O. D. Veloso (DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada)
ABSTRACT This paper investigates how experience of change is construed as meaning by analysing the lexicogrammatical patterns associated with the notion of ‘social transformation’. Through the experiential system of TRANSITIVITY, we analyse instances of the verb ‘transform’ and the nominalization ‘social transformation’ from the COCA corpus. We found two complementary models: a material model of conversion and a relational model of becoming. There are also two complementary models of agency: a middle model, where ‘transforming’ is construed as spontaneous and an effective model, where it is construed as caused by an external Agent. The metaphorical variant ‘social transformation’ displays patterns related to the use of “social” as a Classifier and ‘social transformation’ as part of extending nominal group complexes.